Prevalence and Risk Factors Associated With Hypertension in Hemophilia: Cross-Sectional Analysis of a National Discharge Register. (October 2017) - Seaman, Craig D.; Apostolova, Mariya; Yabes, Jonathan; Comer, Diane M.; Ragni, Margaret V.
Introduction: Improved life expectancy of persons with hemophilia (PWHs) has led to a greater interest in the role of age-related chronic diseases, such as hypertension, in this cohort. Several observational studies have reported an increased prevalence of hypertension in PWHs; however, this has not been assessed using a large, national database in the United States. Aims: We hypothesized the prevalence of hypertension is increased in PWHs and compared the prevalence of hypertension and associated risk factors among patients with and without hemophilia. Methods: A cross-sectional analysis was performed using discharge data among adult males from the National Inpatient Sample over the 3-year period, 2009 to 2011. Hypertension was compared across groups using Rao-Scott χ 2 test. Multivariable logistic regression was used to estimate the odds of hypertension in patients with hemophilia after adjustment for hypertension-associated risk factors. Results: The prevalence of hypertension in patients with hemophilia was less than the prevalence of hypertension in patients without hemophilia (39.5% vs 56.3%, P < .001). Hemophilia was associated with a decreased odds of hypertension after adjusting for associated risk factors (odds ratio: 0.87; 95% confidence interval: 0.81-0.94). Conclusion: In contrast to the findings of several other recent studies, we report a decreased prevalence of hypertension in PWHs. The discrepancy among the reported prevalence of hypertension in our study and several others highlights the potential biases inherent to retrospective and cross-sectional studies and underscores the need for well-designed prospective studies to determine the true incidence of hypertension in PWHs, which may lie somewhere in between our findings and the findings of others.